Peran Persepsi Generative Artificial Intelligence dalam Memediasi Pengaruh Digital Presence Terhadap Brand Visibility Mall di Bali pada Konteks Ai-Based Search - Ida Bagus Gede Prabawa Putra Udiyana; I Gusti Ayu Agung Istri Dinda Larasshanti Jelantik; Anak Agung Ayu Rika Putri Supartha; I Gusti Ayu Widya Ari Cahyathi; Ni Putu Dhanan Kumaradewi M (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the mediating role of perceived generative artificial intelligence in the relationship between digital presence and brand visibility of shopping malls in Bali within the context of AI-based search. The research adopts a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a sample of 130 mall visitors in Bali who have experience using AI-based search tools such as ChatGPT and similar platforms. The findings reveal that digital presence has a positive and significant effect on brand visibility, both directly and indirectly through perceived usefulness and perceived trustworthiness. However, the direct effect of digital presence is relatively weaker compared to the mediated effects, indicating that brand visibility is not formed linearly but through a cognitive information processing mechanism influenced by AI perception. Perceived trustworthiness shows a stronger mediating effect than perceived usefulness, highlighting the importance of trust in AI-generated information. This study contributes to the integration of Information Processing Theory (IPT) and Technology Acceptance Model (TAM) by positioning generative AI perception as a key mechanism in transforming digital presence into brand visibility in the AI-based search ecosystem.